A Skills beyond School Review of the Netherlands - Fazekas, Mihály (OECD Reviews of Vocational Education and Training, 2014)
Vocational education and training (VET) programmes are facing rapid change and intensifying challenges. How can employers and unions be engaged? How can workbased learning be used? How can teachers and trainers be effectively prepared? How should postsecondary programmes be structured? This country report on the Netherlands looks at these and other questions